Flexible Coherence: Re-Thinking e-Learning Design Principles for Linguistically and Culturally Diverse Students - Wiggins, Bradley E. (Contemporary educational technology, 2013)
This article presents the results from a post-test only experiment conducted in 2011 with undergraduate and graduate students (N=67) from individualist and collectivist cultures. Demographic information was collected through questions appearing at the end of a post-test administered to subjects after completing the e-learning module. Each person was randomly assigned to one of three e-learning modules which all shared identical instructional content: time travel. However, the modules differed in design. Specifically, while the control module was designed according to the coherence principle, one experimental module was designed with non-essential background music and the other was designed with non-essential background images. The coherence principle of multimedia instruction stipulates that the addition of extraneous audio, images, or text impairs learning. Nevertheless, one normative standard of multimedia design does not apply to a group of culturally and linguistically diverse learners. Among the findings from this study, a flexible coherence principle is proposed and it suggests that the multimedia designer must consider one’s own cultural and linguistic composition as well as that of the intended audience. A concluding discussion suggests that cultural variation may be related to cognitive variation.